Ageing and women in India - Karkal, Malini (1999)
The Indian population has been ageing over the years, the proportion of older people has been growing. But this increase in life expectancy will not be an unqualified success until adequate provision for the care of the elderly is made. At present, the elderly often suffer abuse and, as in any group, women suffer worse than men. - Reproduced
Keywords: Women - India; Old age - India; Ageing - India; Elderly - India; Elderly